PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI SEKTOR BARANG KONSUMSI DAN ANEKA INDUSTRI DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Rochmat, Claudia Russita; Nurlaela, Siti (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this study is to examine and analyze the effect of financial ratios such as earnings per share (EPS), return on equity (ROE), return on assets (ROA), and net profit margin (NPM) on stock prices in the consumer goods industry sector and various industries in Indonesia for the period of 2013 to 2017. The sample in this study were 63 industrial companies in the consumer and multifarious goods industry in 2013 to 2017 which were selected by purposive sampling method. The analytical method used is multiple analysis using SPSS version 15.0. The results of this study indicate that EPS variables partially have a positive and significant effect on stock prices, while other variables have no effect.